2002
DOI: 10.1152/ajprenal.00327.2001
|View full text |Cite
|
Sign up to set email alerts
|

The electrical resistance breakdown assay determines the role of proteinases in tumor cell invasion

Abstract: The electrical resistance breakdown of the Madin-Darby canine kidney (MDCK) cell monolayer provides a continuous assay system for cancer invasion that detects functional changes before morphological alterations. In this study, we address the question of whether physical contact between tumor cell and epithelial monolayer is a prerequisite for tumor cell invasion. When human melanoma cells were seeded directly (i.e., physical contact) on top of an electrically tight epithelial cell layer (5,800 ± 106 Ω · cm2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…In the first set of experiments we investigated the invasive properties of all three cell lines with an electrophysiological cell-based invasion assay previously established in our laboratory 24,25 . One of the key features of this assay is the high sensitivity to evaluate very early steps of invasion 26 . Although the invasive behaviour of the three cell lines was comparable in siCon cells, we found that knockdown of HPSE attenuates the invasive properties in BLM and MV3 cells as indicated by a delayed decrease of electrical resistance (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first set of experiments we investigated the invasive properties of all three cell lines with an electrophysiological cell-based invasion assay previously established in our laboratory 24,25 . One of the key features of this assay is the high sensitivity to evaluate very early steps of invasion 26 . Although the invasive behaviour of the three cell lines was comparable in siCon cells, we found that knockdown of HPSE attenuates the invasive properties in BLM and MV3 cells as indicated by a delayed decrease of electrical resistance (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that MMP-2 and MMP-9 secreted from melanoma cells are strongly involved in the breakdown of TEER 25,26 . Therefore, we analyzed the secreted amounts of both proteinases in supernatants of melanoma cells by gelatin gel zymography.…”
Section: Knockdown Of Hpse Enhances the Expression Of Mmp But Reducesmentioning
confidence: 99%
“…The quantification of proteolytic activity in vitro and even more in situ is hampered by two major obstacles: excessive posttranslational regulation and spatial restriction (Fig. 12b), both of which are major topics of ongoing research themselves [85,88,89,136].…”
Section: Cellular Microecology and Proteolytic Activitymentioning
confidence: 99%
“…As a result, protease action must obviously occur in the immediate cellular surrounding to contribute to the regulation of the pericellular microenvironment [89]. Not surprisingly, mechanisms that confine and concentrate protease activity in the pericellular space have been found to be essential in tumor cell invasion [85,88]. Among others, these mechanisms comprise the expression of membrane-anchored proteases and receptors for soluble ones by cancer cells [85,86].…”
Section: Cellular Microecology and Proteolytic Activitymentioning
confidence: 99%
“…An epithelial MDCK-C7 cell monolayer serves as a test barrier for malignant cells and develops a high transepithelial electrical resistance (TEER), which can be measured continuously using STX-2 electrode (WPI, Sarasota, FL). Added invasive cells will disturb monolayer integrity followed by decrease and breakdown of TEER (23,31). C7 cells were grown in membrane filter cups (growth area, 4.2 cm 2 ; pore diameter, 0.4 m; thickness, 20 m; Falcon, Heidelberg, Germany).…”
Section: Melanoma Cells and Madin-darby Canine Kidney Cells (Mdck)-c7mentioning
confidence: 99%